Developments and Applications of Nanocellulose-Based Hydrogels in the Biomedical Field - Junidah, Lamaming; Sofie Zarina, Lamaming; Mohd Hazim, Mohamad Amini; Abu Zahrim, Yaser (CRC PRESS, 2023)
Cellulose as an abundant biopolymer has attracted more applications in various industries. Owing to their excellent properties, cellulose can be used individually or with other combinations of materials to improve their properties and meet the standard for targeted applications. Nanocellulose and its cellulose derivatives broaden the scope of research by utilizing advanced technology and science in modification and functionalization. Nanocellulose in hydrogel form is a versatile material that may be molded to fit a wide range of substrates. Along with their mucoadhesiveness, flexibility, swelling, and deswelling responses to environmental stimuli, these properties make nanocellulose-based hydrogels promising candidates for biological applications. This chapter discusses and summarizes the recent development of nanocellulose-based hydrogels, including their structural and unique properties, to be applied in biomedical applications. In recent years, nanocellulose has been made into hydrogels and applied in drug delivery, tissue engineering, wound dressing, and wound healing. This review will highlight some of these applications